Pelatihan Perhitungan Aset pada Home Industri di Desa Muara Penimbung - Sri Maryati; Alieftiyani Paramita Gobel; Eko Pebryan Jaya; Meita Rahmawati (Sriwijaya Accounting Community Services, 2024)
Assets play an important role in organizational operations and assets are needed that can be utilized effectively and efficiently in order to support organizational performance and generate income. Considering the importance of assets, management must be proactive in understanding the existence of assets, identifying, calculating and recognizing the assets they own. Muara Penimbung Village, which is a village supported by Sriwijaya University, is familiar with songket MSMEs. The diversity of educational backgrounds and community livelihoods is one of the factors that makes songket MSMEs in Muara Penimbung Village need understanding and knowledge regarding assets